Neke teoreme o nepokretnoj tački preko γ-ψS kontrakcija na S-metričkim prostorima - Tas, Nihal; Kaplan, Elif (Vojnotehnički glasnik / Military Technical Courier, 2025)
In this paper, the authors introduce generalized contractive conditions on % S -metric spaces, aiming to expand the existing theory of fixed points in such spaces. They apply these new contractive conditions to prove several fixed-point theorems, including integral-type fixed-point results. Additionally, they employ a geometric approach to derive new fixed-circle theorems on S-metric spaces, providing necessary examples to illustrate these results. In the concluding section, the paper highlights the significance of these findings, particularly in the context of activation functions, emphasizing the potential applications of their work in areas like computational mathematics and neural networks.